Stalker [videorecording (DVD)] - Watt, Chris; Skelton, Sophie, 1994-; Brennan, Stuart; Hart, Bret (Gravitas Ventures, 2022)
A broken down freight elevator precariously hangs dangerously high, trapping a young woman inside with her stalker.